An Intrabody Based on a Llama Single-domain Antibody Targeting the N-terminal α-Helical Multimerization Domain of HIV-1 Rev Prevents Viral Production - Vercruysse, Thomas (American Society for Biochemistry and Molecular Biology, 2010)
The human immunodeficiency virus, type 1 (HIV-1)-encoded Rev protein is essential for the expression of late viral mRNAs. Rev forms a large organized multimeric protein-protein complex on the Rev response element of these viral mRNA species and transports them from the nucleus to the cytoplasm, exploiting the CRM1-mediated cellular machinery. Here we report the selection of a nanobody, derived from a llama heavy-chain only antibody, that efficiently blocks the assembly of Rev multimers. The nanobody inhibits HIV-1 replication in cells and specifically suppresses the Rev-dependent expression of partially spliced and unspliced HIV-1 RNA. In HIV-susceptible cells, this nanobody thus has potential as an effective anti-HIV agent using genetic immunization strategies. Its binding site was mapped to Rev residues Lys-20 and Tyr-23 located in the N-terminal α-helical multimerization domain. In the presence of this nanobody, we observed an accumulation of dimeric Rev species, supporting a head-to-head/tail-to-tail molecular model for Rev assembly. The results indicate that the oligomeric assembly of Rev follows an ordered stepwise process and identify a new epitope within Rev that could guide strategies for the development of novel HIV inhibitors.